Women’s Studies 2.0. Italian Feminist Scholarship in the Digital Age. - Hajek, Andrea (Women's History Review, 2017)
The Italian women’s movement of the 1970s was one of the largest and most diverse in Europe. However, after the movement's decline in the late 1970s, scholarly interest in women studies and in the history of second-wave feminism has primarily been upheld through the creation and promotion of women's archives, documentary centres and libraries. More recently, new generations of women have engaged in battles for women's rights, debates about gender issues and feminist scholarship, relying increasingly on new media technologies and social media. It is tempting to conclude that the generation gap that so often marks the relationship between different feminist generations is enhanced by such a technological divide. This article, instead, challenges this assumption by studying the case of an information-based organization that was created in the early 1980s by a group of local feminists in the Italian city of Bologna, and which adopted a strongly digital approach to historical scholarship in the early 1990s. What is the impact of a similar, digital approach to women's history on the nature of historical scholarship and the shape of the archive? Can the digital break through academic hierarchies and institutional barriers, and give a voice to those who have long remained outside of official historiography?